Body‐Wave Tomographic Imaging of the Turkana Depression: Implications for Rift Development and Plume‐Lithosphere Interactions. (9th August 2021) - Kounoudis, R.; Bastow, I. D.; Ebinger, C. J.; Ogden, C. S.; Ayele, A.; Bendick, R.; Mariita, N.; Kianji, G.; Wigham, G.; Musila, M.; Kibret, B.
Abstract: The Turkana Depression, a topographically subdued, broadly rifted zone between the elevated East African and Ethiopian plateaus, disrupts the N–S, fault‐bounded rift basin morphology that characterizes most of the East African Rift. The unusual breadth of the Turkana Depression leaves unanswered questions about the initiation and evolution of rifting between the Main Ethiopian Rift (MER) and Eastern Rift. Hypotheses explaining the unusually broad, low‐lying area include superposed Mesozoic and Cenozoic rifting and a lack of mantle lithospheric thinning and dynamic support. To address these issues, we have carried out the first body‐wave tomographic study of the Depression's upper mantle. Seismically derived temperatures at 100 km depth exceed petrological estimates, suggesting the presence of mantle melt, although not as voluminous as the MER, contributes to velocity anomalies. A NW–SE‐trending high wavespeed band in southern Ethiopia at < 200 km depth is interpreted as refractory Proterozoic lithosphere which has likely influenced the localization of both Mesozoic and Cenozoic rifting. At < 100 km depth below the central Depression, a single localized low wavespeed zone is lacking. Only in the northernmost Eastern Rift and southern Lake Turkana is there evidence for focused low wavespeeds resembling the MER, that bifurcate below the Depression and broaden approaching southern Ethiopia further north. These low wavespeeds may be attributed to melt‐intruded mantle lithosphere or ponded asthenospheric material below lithospheric thin‐spots induced by the region's multiple rifting phases. Low wavespeeds persist to the mantle transition zone suggesting the Depression may not lack mantle dynamic support in comparison to the two plateaus. Plain Language Summary: How continents rift apart to form new oceans through geological time has been debated since the advent of plate tectonic theory. Rifting is currently active in East Africa, where breakup of the African continent is generally occurring in narrow rift valleys. Complicating this picture is the unusually broad and low‐lying Turkana Depression, between the uplifted Ethiopian and Kenyan plateaus. How rifting in Ethiopia and Kenya connects across this region remains elusive. Also unclear is whether the Depression's low elevations are due to a previously stretched plate or the absence of buoyant hot mantle—"plumes." Utilizing data from a new network of seismograph stations, we use the arrival times of seismic energy from distant earthquakes to image the mantle below the Turkana Depression. Most surprisingly, we illuminate a fragment of refractory, ancient plate, trapped in the shallow mantle below southern Ethiopia, which has likely influenced past and present‐day rifting within the Depression. Our images also reveal that the Depression is underlain by deep‐seated, hot, partially molten, buoyant mantle that ponds below variably thinned plate. The Turkana Depression, therefore, does not lack dynamic mantle support in comparison to the uplifted plateaus to the north and south. Key Points: A high wavespeed band in southern Ethiopia marks refractory Proterozoic structure that influenced Mesozoic and Cenozoic strain localization Shallow low wavespeeds mark zones of melt‐intruded lithosphere or ponding asthenosphere beneath variably thinned lithosphere Low mantle wavespeeds are continuous below East Africa, arguing against interpretations that the Depression lacks buoyant dynamic support